Learning Strategies Used By Male and Female Students In Developing English: A Case Study at Sahid University of Surakarta - Dian Muhammad Rifai; Musta’an (STIE AAS Surakarta, 2019)
This study is aimed at analyzing the learning strategies used by male and female students in developing English at Sahid University of Surakarta. This study is a qualitative research in the type of case study. Seventh grade students participated as the respondent to fill the questionnaire and ten students (5 male and 5 female) as the respondents of the interview. The qualitative data are obtained from the result of questionnaire, interview and classroom observation and the document. The data collected of interview and observations are presented in the form of tables. Source and technique triangulations are used to get the trustworthiness of this data. Furthermore, Flowchart Model proposed by Miles and Huberman is applied in this study. The result of the study , such as (1) The male and female students use all kind of strategies in the different frequency (1) The female students tend to use all type of the strategies more frequently than the male students.